Incidence of bacteremia after chewing, tooth brushing and scaling in individuals with periodontal inflammation - Lone Forner (journal of clinical periodontology, 2006)
Scientific rationale for study: Bacteremia occurs with various frequency after oral procedures. Periodontal disease may affect the incidence, magnitude, duration and bacterial spectrum of bacteremia. Principle findings: The incidence and magnitude of bacteremia after scaling was significantly higher in periodontitis than in gingivitis patients and healthy control individuals. In periodontitis patients, the magnitude of bacteremia was associated with gingival index, plaque index and number of sites with bleeding on probing, but not with probing pocket depth measurements. Practical implications: The prevention and treatment of periodontal diseases appear to be crucial for the prevention of bacteremia associated with oral procedures.